A rare case of a spontaneously ruptured secondary hepatic malignant lymphoma - Oshita, Ko (Surg Case Rep, 2018)
BACKGROUND: Although secondary liver involvement of the lymphoma is common and occurs in 50% of patients with non-Hodgkin’s lymphoma, liver tumor rupture in malignant lymphoma is extremely rare. We report a case of a spontaneously ruptured secondary liver involvement of non-Hodgkin’s lymphoma that was successfully treated with transcatheter arterial embolization (TAE) to obtain hemostasis, and subsequent hepatectomy and systemic chemotherapy. To the best of our knowledge, this is only the second reported case of a ruptured hepatic lymphoma. CASE PRESENTATION: A 74-year-old man with sudden-onset right shoulder and upper quadrant pain was transferred to our hospital via an ambulance. His vital signs were stable. Contrast-enhanced computed tomography showed a large hypo-enhancing tumor (94 × 81 mm) in the posterior segment of the liver, with intratumoral extravasation and a 12 × 10 mm daughter tumor in segment 5 of the liver. Hemoperitoneum due to rupture of hepatocellular carcinoma with intratumoral hemorrhage was suspected, although the serum alpha-fetoprotein and protein induced by vitamin K absence-II levels were within normal range. TAE was used for hemostasis. Extended posterior segmentectomy including tumor resection in segment 5 was performed on day 23 after embolization. The postoperative course was uneventful. Pathological examination of the resected specimens revealed that the ruptured tumor was diffuse large B-cell lymphoma. Postoperative fluorodeoxyglucose positron emission tomography-computed tomography showed uptake in the left parotid gland, pancreas, and thoracic vertebra. Based on these findings, the final diagnosis was a ruptured secondary hepatic malignant lymphoma. Complete remission was achieved with chemotherapy. He remains alive 30 months after hepatectomy without evidence of relapse. CONCLUSIONS: We report the first case describing a hepatic tumor rupture as the first presentation of a primary or secondary hepatic malignant lymphoma. The patient was successfully treated with TAE, hepatectomy, and subsequent systemic chemotherapy for non-Hodgkin’s lymphoma.